STRATEGI KEUNGGULAN BERSAING INDUSTRI PARIWISATA DALAM PENGUATAN EKONOMI LOKAL DI KAWASAN SOLO RAYA - Marsudi, Hidup; Nurtantiono, Andri; Kurnianingsih, Heny (Riset Manajemen dan Akuntansi, 2022)
The achievement of competitive advantage will be realized through superior products, namely products that are the choice of consumers. Solo Raya formerly known as Subosukawonosraten (Surakarta, Boyolali, Sukoharjo, Wonogiri, Sragen and Klaten) has a variety of tourism products that are quite unique. Each region has its own characteristics that are difficult for other regions to follow.Based on the regression analysis that the satisfaction of tourist visitors is positively and significantly influenced by the service quality dimension variables, either jointly or partially. Variables in the service quality dimension determine the effect of satisfaction, while variables outside the service quality dimension do not significantly affect the level of satisfaction.Tourist visitors in general, from the aspect of attractiveness, it can be seen that tourist visitors are interested in aspects of the natural environment and socio-cultural environment, from the aspect of advice, tourist visitors prefer a clean, tidy From the aspect of the frequency of visits, most of them visit repeatedly, from the aspect of superior products, most of them are culinary and handicraft products